An Exploration of the Alignment of Learning Theories with eTools at the University of the Western Cape (UWC) - , Juliet Stoltenkamp, André Siebrits, Valentino van de Heyde (Archives of Current Research International, 2017)
The impact of emerging technologies on authentic learning in higher education remains a core concern in the South African context. Learning Management Systems (LMSs) must include emerging technologies to support innovative teaching and learning practices, given their importance in expanding student access to learning materials, and the facilitation of student development. At the University of the Western Cape (UWC), the Centre for Innovative Education and Communication Technologies (CIECT) has championed the adoption of innovative eLearning practices for over 10 years. This study explores the infusion of learning theories aligned to eTools in service of national higher education imperatives. The authors discuss the value of learning theories in the eLearning field, and deliberate on the development of the main learning theories. The study also discusses the application of learning theories in online environments, and this issue is explored by way of six cases, providing examples of how various learning theories can be aligned to eTools. These were gathered from CIECT’s marketing blog, which constitutes a research repository of practitioner experiences and reflections of the institutional LMS and innovative teaching and learning practices. The aim is to explore and emphasize the importance of grounding emerging eTools use in theory and pedagogy to promote student development, as well as the application of learning theories, specifically when designing learning environments to support traditional teaching and learning practices. The qualitative study is primarily exploratory and descriptive. It also includes a brief discussion of the results of a student questionnaire (179 respondents from across faculties and departments) exploring how and why students use eTools at UWC. This exploration of broader student eTools use will help create the foundation for a follow-up study to explore the use of learning theories in promoting more focused eTools adoption.